Perkembangan Bisnis Model Canvas FnB Berbasis Start-up Pada Gen-Z Di Kota Blitar - Luluk Anggraeny Suryandari; Iva Khoiril Mala (Journal of Management and Social Sciences, 2024)
This research aims to discuss the development of the canvas business applied by Gen-Z in start-up businesses. This research method uses a qualitative approach with a business model canvas which is needed to design and build a model concept that can be understood. The results of this research are the development of the canvas business, which is one way for the FnB business to compete by creating good and appropriate business development strategies,- so that the company has a good business model. Good recommendations or suggestions for FnB business development are needed to design and build a business model concept for company development. The canvas model business innovation strategy and marketing strategy model play a significant role in the sustainability of a company as a guide to achieving a goal. This research activity plays an important role for Gen-Z as young entrepreneurs in the FnB sector. The results of this research are for the development and utilization of start-up-based FnB business opportunities among gen-z in the city of Blitar which shows progress.